2022
DOI: 10.3390/agronomy12020335
|View full text |Cite
|
Sign up to set email alerts
|

Cultivar Mixture Enhances Crop Yield by Decreasing Aphids

Abstract: The reduction in biodiversity owing to agricultural intensification has brought negative effects on sustainable crop production in the agro-environment. Plant diversity can help regulate insect pests; however, research that demonstrates that genotypic diversity of multiple varieties with prominent agroecological practices to suppress insect pests and benefit crop yield at agricultural landscapes is limited. To examine the effects of diversity of wheat varieties on aphids and crop productivity, we performed fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The use of a mixture of varieties instead of one variety as a method of controlling insects, such as aphids, is recommended by a number of scientists, as they note a decrease in the number of pests and an increase in crop yield [DUAN 2022;GRETTENBERGER, TOOKER 2017].…”
Section: Discussionmentioning
confidence: 99%
“…The use of a mixture of varieties instead of one variety as a method of controlling insects, such as aphids, is recommended by a number of scientists, as they note a decrease in the number of pests and an increase in crop yield [DUAN 2022;GRETTENBERGER, TOOKER 2017].…”
Section: Discussionmentioning
confidence: 99%
“…The authors also found that predation in nonorganic (conventional) fields was higher than in organic fields within simple landscapes. In a recent study, the abundance of S. miscanthi and R. padi was decreased when five different varieties of winter wheat were sown in a field [241]. Different wheat genotypes can also determine aphid abundance.…”
Section: Effect Of Agricultural Practices and Environmentmentioning
confidence: 99%
“…This is shown very clearly in reduced Rhynchosporium infection in winter barley which is directly proportional to the number of components in the mixture, and greater component number leads to yield increase even in the absence of disease (Newton et al, 1997). Similarly, aphid abundance was lower in wheat cultivar mixtures, with no yield impairment (Duan et al, 2022). However, a small amount of particular varieties in an intra-specific mixture of plants can contribute a disproportionately large effect on the function of the mixture for some outcomes such as disease reduction (Newton and Skelsey, 2023), so the nature of such responses is likely to be trait specific.…”
Section: Examples Of Diversity Conceptsmentioning
confidence: 99%